The effect of return on assets (ROA), return on equity (ROE), debt to equity ratio (DER) on stock prices in property companies listed on the indonesia stock exchange - Oktavianti, Santi; Mesra, Mesra; Haqiqi, Teuku Muhammad; Shalahuddin, M.; Rahmania, Vanesha; Oktaviyani, Henny (Institute of Computer Science (IOCS), 2024)
This study aims to determine the effect of return on assets (ROA), return on equity (ROE) and Debt to equity (DER) on stock prices of property stocks in Indonesia for a period of 4 years (2019-2022). This research is quantitative research. The data used in this research is secondary data. Sampling in this study used a purposive sampling technique in order to obtain 32 companies as research samples. Data taken from financial reports listed on the Indonesia Stock Exchange (IDX). Data analysis using panel data analysis with the selected regression model is the fixed effect model. The results showed that partially the ROA variable had a positive and insignificant effect on stock prices, ROE had a negative and insignificant effect on stock prices, DER had and a negative and significant effect on stock prices